Differences in glucose level between right arm and left arm using continuous glucose monitors. (November 2020) - Kim, Nicole; Pham, Kevin; Shek, Allen; Lim, Jeremy; Liu, Xiaohan; Shah, Sachin A
Background: Continuous glucose monitoring (CGM) measures interstitial glucose levels through a sensor with a thin filament inserted under the skin. It is customary for patients to rotate sensor application sites between arms to minimize skin irritation. However, there is limited data regarding the degree of inter-arm differences with CGM technology. Methods: Self-proclaimed right-handed (n = 5) and left-handed (n = 5) participants, regardless of concurrent comorbidities, were enrolled for CGM. Participants wore a FreeStyle Libre Pro sensor on each arm for a maximum of 14 days. Muscle mass and body fat analysis was conducted using a multi-frequency segmental body composition analyzer. Glucose levels from both arms were time-matched with the first 12 hours eliminated from analysis. Mean glucose and time in target range were compared between readings from the right and left arm. Results: A total of 9830 paired glucose levels were included for analysis. In all participants (n = 10), mean glucose on the right arm was 89.1 mg/dL (SD, 19.9) and 85.3 mg/dL (SD, 19.3) on the left arm (P < 0.001). Glucose was out of target range (70-180 mg/dL) for 12.7% of the time in the right arm compared to 18.5% in the left arm (P < 0.001). Conclusions: In a group of 10 nondiabetic and diabetic adults, there was a statistically significant difference in CGM readings between the right and left arms. Time in target range may differ based on arm selection when using a CGM. Arm dominance did not explain the inter-arm glucose level discordance.